2018
DOI: 10.1242/dev.163477
|View full text |Cite
|
Sign up to set email alerts
|

Bsx controls pineal complex development

Abstract: Neuroendocrine cells in the pineal gland release melatonin during the night and, in teleosts, are directly photoreceptive. During development of the pineal complex, a small number of cells migrate leftward away from the pineal anlage to form the parapineal cell cluster, a process that is crucial for asymmetrical development of the bilateral habenular nuclei. Here, we show that, throughout zebrafish embryonic development, the () gene is expressed in all cell types of the pineal complex. We identified Bmp and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 65 publications
4
43
1
Order By: Relevance
“…To examine the ontogenetic expression patterns of Bsx , in situ hybridization was performed on coronal brain sections from rats sacrificed at daytime (ZT6) and at nighttime (ZT18) during pre‐ and postnatal stages ranging from E15 to P30 (Figure ). Bsx was detected in the pineal gland at all ages, as reported in other species, but was undetectable in other brain regions present in the same coronal plane. Both developmental age and ZT exerted significant effects on Bsx expression in the pineal gland ( P < .0001) (Figure ).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…To examine the ontogenetic expression patterns of Bsx , in situ hybridization was performed on coronal brain sections from rats sacrificed at daytime (ZT6) and at nighttime (ZT18) during pre‐ and postnatal stages ranging from E15 to P30 (Figure ). Bsx was detected in the pineal gland at all ages, as reported in other species, but was undetectable in other brain regions present in the same coronal plane. Both developmental age and ZT exerted significant effects on Bsx expression in the pineal gland ( P < .0001) (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…Current knowledge establishes a role of Bsx in development of the pineal gland in several vertebrate species; in addition, genome‐wide large‐scale screening efforts suggest rhythmic expression of Bsx in the mature pineal gland of the rat . The present study expands upon this knowledge by exploring persistent ontogenetic expression, cellular localization, regulation, and molecular role of Bsx in the rat pineal gland, as well as anatomical distribution of BSX transcripts in the human pineal gland.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The bsx transcription factor is expressed in several domains within the secondary prosencephalon in mouse and zebrafish (Cremona et al, 2004;Schredelseker and Driever, 2018). Here, comparing bsx expression with arxa as a marker for the alar territories, we found that most bsx expression in the ventral forebrain is restricted to the basal plate (Figures 2A-A ,H).…”
Section: Bsx Is Expressed In Both Tuberal and Mamillary Regions Of Thmentioning
confidence: 77%
“…For all probes which have been described previously, references are given in Supplementary Table S1. Templates for all other probes were PCR amplified from cDNA and subcloned into pCRII-TOPO plasmid (Invitrogen) as has been described before (Schredelseker and Driever, 2018). Primer sequences are shown in Supplementary Table S1.…”
Section: Cloning Of Cdna Fragments For Probe Synthesismentioning
confidence: 99%